2008
DOI: 10.1073/pnas.0712125105
|View full text |Cite
|
Sign up to set email alerts
|

SNAREpin/Munc18 promotes adhesion and fusion of large vesicles to giant membranes

Abstract: Exocytic vesicle fusion requires both the SNARE family of fusion proteins and a closely associated regulatory subunit of the Sec1/ Munc18 (SM) family. In principle, SM proteins could act at an early SNARE assembly step to promote vesicle-plasma membrane adhesion or at a late step to overcome the energetic barrier for fusion. Here, we use the neuronal cognates of each of these protein families to recapitulate, and distinguish, membrane adhesion and fusion on a novel lipidic platform suitable for imaging by fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
87
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 46 publications
2
87
0
Order By: Relevance
“…Whereas Munc18a inhibits complex formation of soluble SNARE proteins (1), Munc18a facilitates SNARE assembly with Syx1a immobilized through its C terminus to affinity resin (3) and stimulates lipid mixing of liposomes containing full-length SNARE proteins (4)(5)(6)(7)20). Recent work has demonstrated that Munc18a also reduces lipid mixing of SNARE-embedded liposomes, in line with its inhibitory effect on SNARE assembly in solution (7).…”
Section: *Derived From Crysol (30)mentioning
confidence: 90%
“…Whereas Munc18a inhibits complex formation of soluble SNARE proteins (1), Munc18a facilitates SNARE assembly with Syx1a immobilized through its C terminus to affinity resin (3) and stimulates lipid mixing of liposomes containing full-length SNARE proteins (4)(5)(6)(7)20). Recent work has demonstrated that Munc18a also reduces lipid mixing of SNARE-embedded liposomes, in line with its inhibitory effect on SNARE assembly in solution (7).…”
Section: *Derived From Crysol (30)mentioning
confidence: 90%
“…Munc18-1 has been shown to play dual roles in synaptic vesicle fusion. First, Munc18-1 positively regulates the SNARE-dependent fusion reaction by interacting with the trans-SNARE complex and accelerating the fusion kinetics (12,(25)(26)(27)(28)(29)(30)(31)(32)(33). Second, Munc18-1 binds to syntaxin-1 monomer and locks the latter into a "closed" configuration that prevents SNARE complex formation (34-36).…”
mentioning
confidence: 99%
“…The most intensely studied form of intracellular membrane fusion is calcium-triggered neurotransmitter release at the chemical synapse, which serves as the brain's major form of cell-cell communication (15)(16)(17)(18)(19). Neurotransmitter secretion is mediated by the fusion of exocytic vesicles with the plasma membrane and requires the v-SNARE vesicle-associated membrane protein 2 (VAMP2; also known as synaptobrevin-2), the t-SNAREs syntaxin-1 and soluble N-ethylmaleimide-sensitive factor attachment protein (SNAP)-25, and the SM protein Munc18-1/ nSec1 (UNC-18 in nematodes and ROP in flies) (20)(21)(22)(23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%